2012
DOI: 10.1310/tsr1903-212
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Effects of Training-Induced Visual Field Recovery in Patients With Chronic Stroke

Abstract: White stimulus training-induced VFE can lead to improved color and shape perception and to increased reading speed in and beyond the pretraining transition zone if ECSG is sufficiently large. The latter depends on the eccentricity of the VFE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Bergsma and colleagues also reported transfer from RFT detection training to flicker fusion, color, form and reading ability in 3 patients following training (Bergsma and van der Wildt 2008). In a follow-up study, 9/12 subjects showed an improvement in reading speed, while 3/7 showed an improvement in color and shape discrimination, though one of these 3 subjects exhibited poor fixation (Bergsma and others 2012). In short, perimetry-like detection training appears to transfer to untrained stimuli, but the reason why it transfers for some CB patients and not others remains unclear.…”
Section: How Normal Is Recovered Vision?mentioning
confidence: 98%
See 2 more Smart Citations
“…Bergsma and colleagues also reported transfer from RFT detection training to flicker fusion, color, form and reading ability in 3 patients following training (Bergsma and van der Wildt 2008). In a follow-up study, 9/12 subjects showed an improvement in reading speed, while 3/7 showed an improvement in color and shape discrimination, though one of these 3 subjects exhibited poor fixation (Bergsma and others 2012). In short, perimetry-like detection training appears to transfer to untrained stimuli, but the reason why it transfers for some CB patients and not others remains unclear.…”
Section: How Normal Is Recovered Vision?mentioning
confidence: 98%
“…Figure 2B–I shows the wide range of stimuli and tasks used in these studies. In another important distinction from VRT, most of these groups presented targets fully in the blind field rather than straddling the border between intact and impaired vision, and a significant proportion (Bergsma and others 2012; Bergsma and van der Wildt 2010; Das and others 2014; Huxlin and others 2009; Sahraie and others 2010; Sahraie and others 2013; Sahraie and others 2006) used infrared eye trackers to enforce fixation during testing. The key principle behind this approach was that for visual restitution therapy to work, one had to force the blind field ( not portions of the intact visual field ) to process stimuli using spared cortical circuits that functioned abnormally post-lesion.…”
Section: Can a V1-damaged Visual System Be Retrained To See?mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies reported expansion of the visual field following treatment (Bergsma, Elshout, van der Wildt, & van den Berg, 2012; Mueller et al., 2007; Romano et al., 2008). However, for studies in which fixation was controlled and assessed using the scanning laser ophthalmoscope, little or no change in the visual field area was noted (Marshall, Chmayssani, O'Brien, Handy, & Greenstein, 2010; Reinhard et al., 2005; Sabel et al., 2004).…”
Section: Interventionsmentioning
confidence: 99%
“…However, for studies in which fixation was controlled and assessed using the scanning laser ophthalmoscope, little or no change in the visual field area was noted (Marshall, Chmayssani, O'Brien, Handy, & Greenstein, 2010; Reinhard et al., 2005; Sabel et al., 2004). Despite little or no improvement in the visual field area, patients reported an improvement in quality of life and ADL, such as mobility and reading (Bergsma et al., 2012; Gall & Sabel, 2012; Mueller et al., 2007; Plow, Obretenova, Fregni, Pascual‐Leone, & Merabet, 2012; Sabel et al., 2004). Although not statistically significant, reports of visual hallucination or less dense areas of visual field loss were also more likely to show improvement (Poggel et al., 2007; Sabel et al., 2013).…”
Section: Interventionsmentioning
confidence: 99%